2010
DOI: 10.2528/pier10050609
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Wireless Energy Transmission Using Magnetic Resonance Based on Negative Refractive Index Metamaterial

Abstract: Abstract-In this paper, a high-efficiency wireless energy transmission via magnetic resonance is implemented by using negative permeability metamaterial structures. The metamaterial structure is consisted of a three-dimensional (3D) periodic array of the unit cell that the capacitively loaded split ring resonators (CLSRRs) are periodically arranged in the cubic dielectric surfaces. This metamaterial structure has the negative permeability property that matches free space, which is used as a magnetic flux guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…As electric vehicles make use of large amounts of energy, any loss in energy efficiency due to the energy transfer process from the source to the vehicle, will be significant. It has been found that magnetic resonance coupling based wireless energy transfer system is an effective solution of powering or charging an EV wirelessly [6][7][8][9][10][11][12][13]. As a result of the advantage of being efficient over a relatively far distance, the magnetic resonance coupling based wireless energy transfer system has been utilized for charging EVs.…”
Section: Introductionmentioning
confidence: 99%
“…As electric vehicles make use of large amounts of energy, any loss in energy efficiency due to the energy transfer process from the source to the vehicle, will be significant. It has been found that magnetic resonance coupling based wireless energy transfer system is an effective solution of powering or charging an EV wirelessly [6][7][8][9][10][11][12][13]. As a result of the advantage of being efficient over a relatively far distance, the magnetic resonance coupling based wireless energy transfer system has been utilized for charging EVs.…”
Section: Introductionmentioning
confidence: 99%
“…There had also been studies of anomalous scattering by conducting cylinders coated with metamaterials [9]. Works associated with the studies of unusual resonances caused by metamaterials [10] for achieving improved efficiencies [11], strong field localization [12], and even microwave filtering in waveguides [13] were also conducted. Other interesting applications have also been considered and studied, and a good summary of them can be viewed in recent manuscripts [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, ε and µ are both positive in ordinary materials. The negative permittivity can be obtained by arranging the metallic thin wires periodically [18][19][20][21][22][23][24][25]. Alternatively, an array of split ring resonators (SRRs) can display negative effective permeability.…”
Section: Introductionmentioning
confidence: 99%